Essential and xenobiotic elements in cottage cheese from the Slovak market with a consumer risk assessment. Issue 7 (2nd July 2020) - Capcarova, Marcela; Harangozo, Lubos; Arvay, Julius; Toth, Tomas; Gabriny, Lucia; Binkowski, Lukasz J.; Palsova, Lucia; Skalicka, Magdalena; Pardo, Maria de la Luz Garcia; Stawarz, Robert; Massanyi, Peter
Abstract: The examination of various elements in the milk products is very important in the food sector in respect of food quality and safety. The aim of this study was to determine the concentrations of calcium (Ca), cobalt (Co), cadmium (Cd), copper (Cu), chromium (Cr), iron (Fe), mercury (Hg), potassium (K), magnesium (Mg), sodium (Na), nickel (Ni), phosphorus (P), lead (Pb) and zinc (Zn) in white cottage cheese or cottage cheese supplemented with various additives (white, lacto-free, chive, tzatziki, mustard + onion, chili, active protein) available on the market of Slovakia. All essential elements were within the reference range. Cottage cheese enriched with tzatziki showed higher amount of Cu, Fe, K, and Zn. Mustard + onion cheese contained high values of Ca, Co, Mg, and Ni. In white cottage cheese high amount of Cr, Mn, and P was measured. The content of xenobiotic metals was below permitted limit. The contribution to PTWI (Provisional tolerable weekly intake) suggested very low dietary exposure to heavy metals as Cd, Hg, and Pb as well as other metals (Cu, Ni, and Zn) in cottage cheese. Numerous correlations between concentrations were observed. MOE (Margin of Exposure) evaluation denoted that average consumption of cottage cheese does not pose any high cardiovascular and nephrotoxicity threat.